Silent Tyrosinemia Type I Without Elevated Tyrosine or Succinylacetone Associated with Liver Cirrhosis and Hepatocellular Carcinoma. Issue 10 (8th August 2016) - Blackburn, Patrick R.; Hickey, Raymond D.; Nace, Rebecca A.; Giama, Nasra H.; Kraft, Daniel L.; Bordner, Andrew J.; Chaiteerakij, Roongruedee; McCormick, Jennifer B.; Radulovic, Maja; Graham, Rondell P.; Torbenson, Michael S.; Tortorelli, Silvia; et al.
Abstract : Whole exome sequencing of a family with two siblings who developed hepatocellular carcinoma within months of one another revealed a novel homozygous variant in FAH, the gene mutated in tyrosinemia type I (TYRNS1). The individuals identified with this variant underwent biochemical testing and were found to lack diagnostic elevations of succinylacetone, a specific marker for TYRSN1 that is utilized in newborn screening. Functional validation of this variant established pathogenicity and argues for molecular testing of patients with suggestive clinical presentations. ABSTRACT: Tyrosinemia type I (TYRSN1, TYR I) is caused by fumarylacetoacetate hydrolase (FAH) deficiency and affects approximately one in 100, 000 individuals worldwide. Pathogenic variants in FAH cause TYRSN1, which induces cirrhosis and can progress to hepatocellular carcinoma (HCC). TYRSN1 is characterized by the production of a pathognomonic metabolite, succinylacetone (SUAC) and is included in the Recommended Uniform Screening Panel for newborns. Treatment intervention is effective if initiated within the first month of life. Here, we describe a family with three affected children who developed HCC secondary to idiopathic hepatosplenomegaly and cirrhosis during infancy. Whole exome sequencing revealed a novel homozygous missense variant in FAH (Chr15(GRCh38):g.80162305A>G; NM_000137.2:c.424A > G; NP_000128.1:p.R142G). This novel variant involves the catalytic pocket of the enzyme, but does not result in increased SUAC or tyrosine, making the diagnosis of TYRSN1 problematic. Testing this novel variant using a rapid, in vivo somatic mouse model showed that this variant could not rescue FAH deficiency. In this case of atypical TYRSN1, we show how reliance on SUAC as a primary diagnostic test can be misleading in some patients with this disease. Augmentation of current screening for TYRSN1 with targeted sequencing of FAH is warranted in cases suggestive of the disorder.